Plasmonic CROWs for Tunable Dispersion and High Quality Cavity Modes - Wood,JJ; Lafone,L; Hamm,JM; Hess,O; Oulton,RF (Scientific Reports, 2015)
Coupled resonator optical waveguides (CROWs) have the potential to revolutionise integrated optics, to slow-light and enhance linear and non-linear optical phenomena. Here we exploit the broad resonances and subwavelength nature of localized surface plasmons in a compact CROW design where plasmonic nanoparticles are side coupled to a dielectric waveguide. The plasmonic CROW features a low loss central mode with a highly tunable dispersion, that avoids coupling to the plasmonic nanoparticles close to the band-edge. We show that this low loss character is preserved in finite plasmonic CROWs giving rise to Fabry-Perot type resonances that have high quality factors of many thousands, limited only by the CROW length. Furthermore we demonstrate that the proposed CROW design is surprisingly robust to disorder. By varying the geometric parameters one can not only reduce the losses into dissipative or radiative channels but also control the outcoupling of energy to the waveguide. The ability to minimise loss in plasmonic CROWs while maintaining dispersion provides an effective cavity design for chip-integrated laser devices and applications in linear and non-linear nano-photonics.